2020
DOI: 10.1371/journal.pone.0237558
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe illness in hospitalized Covid-19 patients at a regional hospital

Abstract: Background The Covid-19 pandemic threatens to overwhelm scarce clinical resources. Risk factors for severe illness must be identified to make efficient resource allocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 27 publications
(43 reference statements)
4
34
2
1
Order By: Relevance
“…Only 6.8% of our patients were admitted to ICU during the study period, which contrasts with 17% admission rates reported in earlier Chinese reports [ 13 ] and 30.8% rates reported at rural hospitals in the USA [ 25 ]. ICU admission rates in other Spanish hospitals were 13% [ 22 ]; however, mortality was high, and similar to the rates which we found in our series (72%).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Only 6.8% of our patients were admitted to ICU during the study period, which contrasts with 17% admission rates reported in earlier Chinese reports [ 13 ] and 30.8% rates reported at rural hospitals in the USA [ 25 ]. ICU admission rates in other Spanish hospitals were 13% [ 22 ]; however, mortality was high, and similar to the rates which we found in our series (72%).…”
Section: Discussioncontrasting
confidence: 87%
“…In contrast, patients’ sex was not associated significantly to mortality. While male sex has been revealed as a risk factor for mortality in several studies carried out both in Spain [ 22 ] and other countries [ 11 , 14 , 15 , 18 , 23 , 24 ], it was not in many others [ 17 , 20 , 21 , 25 , 26 , 27 ]. Male sex could act, therefore, as a confounding variable for other risk factors more commonly described among males, such as cardiovascular diseases or tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were from China 5 , 9 , 11 , 16 38 ( n = 26), followed by United States 39 43 ( n = 5), Switzerland 44 , 45 ( n = 2), Japan 8 ( n = 1), Korea 46 ( n = 1), Oman 47 ( n = 1), Qatar 48 ( n = 1), Iran 49 ( n = 1), Denmark 50 ( n = 1), Mexico 51 ( n = 1), and Bulgaria 52 ( n = 1). The sample size of included studies ranged from 41 to 5000 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Additional predictors of mortality were also investigated with multivariate analysis in this study, and age was confirmed as a key player in COVID-19 patients' outcome. Several explanations can be provided to clarify this finding: (1) older adults are more likely to have multiple comorbidities which represent significant risk factors for COVID-19 complications [31]; (2) frailty, defined as a biological syndrome featured by cumulative declines in different physiological systems and resulting in a loss of reserves and resistance to external stressors, is more common in patients aged over 80 years; (3) immune system efficiency is known to decrease during aging, representing a physiological mechanism leading to a higher susceptibility to infections; 4) reduced mobility and autonomy can lead to a delay in access to hospital care [32][33][34][35][36][37]. Interestingly, we observed distinctive patterns when analyzing the results in terms of the presenting symptoms of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%